058 Assessment of the Evidence for Diagnostic Tests and Strategies: A Systematic Review of Available Tools. (15th August 2013) - Mustafa, R; Wiercioch, W; Falavigna, M; Zhang, Y; Prediger, B; Cheung, A; Ivanova, L; Arevalo-Rodriguez, I; Schünemann, H
Abstract : Background: The challenges facing guideline developers when making recommendations about diagnostic tests and strategies (DTS) are considerably different when compared to treatment recommendations. Objectives: To identify, describe and compare all available instruments, checklists, critical appraisal tools, and indices designed for assessing the quality of evidence (QoE) or strength of recommendations (SoR) dealing with diagnostic tests and strategies. Methods: We conducted a comprehensive systematic search of the literature including state of the art diagnostic guidelines, methods papers and diagnostic systematic reviews. Results: We identified 45 tools and modifications of existing tools to assess the QoE and SoR of DTS. Most tools acknowledge the importance of assessing the QoE and SoR separately. Most tools include individual quality criteria and study design but no tool rates all quality criteria suggested by the GRADE working group. Only two tools explicitly consider factors that increase the confidence in the evidence. When moving from evidence to recommendations, patient values and preferences and resources were rarely considered. Discussion: There is confusion about the terminology that describes the various factors that influence the QoE and SoR. The criteria for evaluating the QoE and moving from evidence to recommendations are incomplete for most guideline development frameworks that we evaluated. Implications for Guideline Developers/Users: The GRADE approach is the most complete approach encompassing all factors but users will benefit from a better description of the evidence to recommendation framework in GRADE and clarification of issues that relate to laboratory validity parameters.